Tinjauan geografis wilayah potensial ibukota negara Indonesia - Anugerah A. Sahamony; Luthfi Muta’ali; Estuning Tyas Wulan Mei Mei (Jurnal Teknosains, 2020)
The number of actual problems in the existing capital of Indonesia raises the idea to move the national government center to another region. From all parts of Indonesia republic territory, which region is most potential to be the location of the nation’s capital relocation? The aim of this research is to identify the most potential area to be the location of the national government center development. The method used is this research is a quantitative analysis with ‘zooming’ concept. The analysis process is divided into three stages with nine assessment indicators. The stages are; (1) identifying the most ideal provinces using spatial centrality, external accessibility, and the vulnerability of macro-scale natural disaster variables, (2) identifying the most potential province using the potential of social condition, the potential of infrastructure development, and the potential of national economic integration variables, and (3) determining the most suitable zone to be the location of nation’s capital development, which is using variables of physiological and regulational suitability (land availability, water aviability, and the vulnerability of micro-scale disaster). The results of this research indicate that Paser Distict in Kalimantan Timur is the most potential region to be the future nation’s capital of Indonesia.